Familial hyperaldosteronism type 1 and pregnancy: successful treatment with low dose dexamethasone. (4th March 2021) - Sanga, Viola; Lenzini, Livia; Seccia, Teresa Maria; Rossi, Gian Paolo
Abstract: Purpose: Familial hyperaldosteronism type 1 (FH-1) is an autosomal dominant form of primary aldosteronism (PA), featuring a marked phenotypic heterogeneity, ranging from mild forms of PA and arterial hypertension (HT) to severe forms complicated by stroke at a young age. Affected patients usually reach the fertile age; hence, transmission of the disease to offspring is common. Notwithstanding this, only anecdotal reports of FH-1 in pregnancy exist and recommendations for treatment remain vague. Materials and Methods and Results: We herein report on a novel FH-1 pedigree featuring very severe HT, fatal aortic dissection, and high rate of early stroke, where a young FH-1 woman was successfully managed throughout pregnancy with low-dose dexamethasone. Conclusions: Based on this experience and on available information on pathophysiology of FH-1 in pregnancy, the pros and cons of dexamethasone administration in the treatment of FH-1 in pregnancy are also discussed.